Harnessing the digital records of everyday things - Darzentas, Dimitrios; Hazzard, Adrian; Brown, Michael; Flintham, Martin; Benford, Steve (2016)
We address how, framed by the Internet of Things, digitally-enabled physical objects may acquire rich digital records throughout their lifetimes, and how these might enhance their value, meaning and utility. We reflect on emerging findings from two case studies, one focusing on wargaming miniatures and the other on an augmented guitar, that engage communities of practice in capturing and utilising rich digital records of things. We articulate an agenda for future research in terms of four key themes: How can the digital records of everyday things be captured using both manual and automated approaches? How can these records enhance the embodied use of things in suitably discrete ways? How can people generate diverse stories and accounts from these records? How can we revisit current notions of ownership to reflect a more fluid sense of custodianship? The findings of the studies reveal common emergent themes and preferences of the practicing communities that surround these objects and the above questions, while ongoing participatory and probe studies continue to reveal nuances and evaluate possible approaches.